Effective Separation of CO2 Using Metal‐Incorporated rGO Membranes. Issue 17 (17th March 2020) - Jin, Xiaoheng; Foller, Tobias; Wen, Xinyue; Ghasemian, Mohammad B.; Wang, Fei; Zhang, Mingwei; Bustamante, Heriberto; Sahajwalla, Veena; Kumar, Priyank; Kim, Hangyel; Lee, Gwan‐Hyoung; Kalantar‐Zadeh, Kourosh; et al.
Abstract: Graphene‐based materials, primarily graphene oxide (GO), have shown excellent separation and purification characteristics. Precise molecular sieving is potentially possible using graphene oxide‐based membranes, if the porosity can be matched with the kinetic diameters of the gas molecules, which is possible via the tuning of graphene oxide interlayer spacing to take advantage of gas species interactions with graphene oxide channels. Here, highly effective separation of gases from their mixtures by using uniquely tailored porosity in mildly reduced graphene oxide (rGO) based membranes is reported. The gas permeation experiments, adsorption measurement, and density functional theory calculations show that this membrane preparation method allows tuning the selectivity for targeted molecules via the intercalation of specific transition metal ions. In particular, rGO membranes intercalated with Fe ions that offer ordered porosity, show excellent reproducible N2 /CO2 selectivity of ≈97 at 110 mbar, which is an unprecedented value for graphene‐based membranes. By exploring the impact of Fe intercalated rGO membranes, it is revealed that the increasing transmembrane pressure leads to a transition of N2 diffusion mode from Maxwell–Stefan type to Knudsen type. This study will lead to new avenues for the applications of graphene for efficiently separating CO2 from N2 and other gases. Abstract : Membranes of reduced graphene oxide with interlaced transition metal ions offer effective separation of CO2 from N2 due to higher adsorption of N2 gas molecules within the Fe‐interacted nanochannels. Depending on the value of applied gas pressure, both Maxwell–Stefan and Knudsen diffusion contribute to the gas permeation process for these membranes.